Evaluation the serum levels of T3, T4, TSH, Thyroglobulin and Galactin-3 in patients with benign and malignant thyroid tumors (Journal of Pharmaceutical Negative Results, 2022)
Background: Currently, cytological examination of fine needle biopsies is the method used for preoperative differential diagnosis of thyroid nodules, however, the results may be inaccurate in about 20% of cases. Aim: The study aimed to detect a biomarker in the serum to detect and distinguish between benign and malignant thyroid gland tumors. Methods: Seventy-two patients were divided into malignant thyroid tumor (n = 45) and benign thyroid tumor (n = 27), the median age of patients was 45 years. The blood samples were collected from Middle Euphrates Cancer Center /Al- Najaf Al-Ashraf Governorate in Iraq from September 2019 until March 2020. Every patient's study group was divided into subgroups according to age, gender and body mass index (BMI). A physician diagnosed the patients based on history, clinical presentation and fine needle aspirate. Each patient group was distributed into two groups: before and after thyroidectomy. The control group was made out of sixteen healthy male and females the median of age was 47 years. Results: A significant rise (p0.05) in serum T4 in patients with benign thyroid tumors matched with healthy and malignant thyroid tumor groups could be seen. A significant rise (p0.05) of T3 and T4 concentration in patients with benign thyroid tumor in male groups compared with female groups was observed. A significant increase (p0.05) of T4 concentration in patients with malignant thyroid tumor in BMI group (18-24.9) Kg/m2 compared with other BMI groups was observed. A significant increase (p0.05) of T3 and T4 concentration in patients with benign thyroid tumor in BMI group (18-24.9) Kg/m2 compared with other BMI groups was also observed. Also, serum TSH exhibited a significant increase (p0.05) in patients with malignant thyroid tumors compared with healthy group and benign thyroid tumor group. On other hand the results demonstrated that that there was a significant increase (p0.05) in serum Tg and Galactin-3 of patients with malignant thyroid tumors and benign thyroid tumor group compared with healthy group. Regarding the thyroidectomy, there was a significant increase of TSH (p0.05) in patients with malignant thyroid tumor earlier thyroidectomy matched with that later thyroidectomy. Tg concentration exposed a significant decrease (p0.05) after thyroidectomy compared with groups before thyroidectomy in benign and malignant thyroid tumor. Conclusions: Depending on the findings of the study, we can conclude that the early detection of abnormal biochemical parameters includes TSH, thyroglobulin, and Galactin-3 can limit complication and it can also help to monitor the progression of the disease in patients with thyroid cancers. But, the findings did not demonstrate that these biomarkers could be used to discriminate between malignant and benign thyroid tumor.